PERHITUNGAN CADANGAN HIDROKARBON FORMASI TALANG AKAR MENGGUNAKAN ANALISIS PETROFISIKA DAN SEISMIK INVERSI AI DENGAN PENDEKATAN MAP ALGEBRA PADA LAPANGAN BISMA, CEKUNGAN SUMATERA SELATAN - Egi Ramdhani; Ordas Dewanto; Karyanto Karyanto; Nanang Yulianto (Engineering Faculty Universitas Lampung, 2018)
As a potential field in hydrocarbon prospect, Bisma field, the part of south Sumatra basin, can be evaluated in order to mapping the hydrocarbon accumulation and total reserve calculation purpose. Petrophysical analysis is an analytic method to evaluate the formation which sensitive with vertical contrast. Main output of this analysis is the compilation of some property value that useful on reservoir quality justification. Seismic acoustic impedance inversion is a method that can be used to define the distribution of porous zone as a hydrocarbon reservoir. This inversion result is the distribution of prospect area map by using combination of interpretation in AI map, density map and P-wave map. Map algebra is a calculation method that used to map that has the same grid number. By using those three methods, the reserve of hydrocarbon accumulation on Bisma field can be calculated. Petrophysical analysis results the indication of hydrocarbon in target zone is oil on two main layer, S and W3. Meanwhile, seismic inversion interpreting the distribution of porous zone is between 7400 – 9315 m/s*gr/cc in AI value context. Then, the effective porosity, Sw value and isopach are spread laterally using picked horizon and seismic acoustic impedance result as a guide, also, calculating the reserve. Layer S accumulating 21.1 million barrel oil and W3 accumulating 50.2 million barrel oil. This value resulted by aplicating Original Oil in Place (OOIP) equation on property map with map algebra approachment.